Relational Marketing Agility and Entrepreneurial Marketing in Tourism: A Conceptual Frameworks for Sustainable Competitive Advantage - Sisno Riyoko (Citakonsultindo, 2025)
This conceptual paper develops an integrative model explaining how Relational Marketing Agility (RMA) operates as a mediating dynamic capability that strengthens the linkage between Entrepreneurial Marketing (EM) and Sustainable Competitive Advantage (SCA) in entrepreneurial tourism. Responding to increasingly dynamic tourism environments, shifting customer expectations, and intensified digital-based competition, this study synthesizes insights from Entrepreneurial Marketing, the Dynamic Capabilities View (DCV), relational capability, and agile marketing. Through systematic literature integration, RMA is conceptualized as a higher-order dynamic capability consisting of customer-sensing agility, relational adaptation agility, and rapid response capability. The proposed framework argues that RMA mediates the influence of EM on SCA by enabling tourism firms to identify relational opportunities, adjust engagement strategies, and respond swiftly to evolving customer needs. This model advances theoretical understanding by positioning RMA as a pivotal mechanism that transforms marketing innovativeness into long-term competitive strength within experience-driven tourism markets. As one of the earliest conceptual articulations of RMA in entrepreneurial tourism, the study contributes to dynamic capabilities literature and provides a foundation for future empirical research. It also offers strategic guidance for tourism SMEs aiming to enhance competitiveness through the development of agile relational capabilities